2018
DOI: 10.37358/rc.18.11.6702
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Biomarkers Determination in Alzheimer Dementia

Abstract: Alzheimer�s disease (AD) is a complex neuropsychiatric condition characterized by progressive cognitive symptoms.The social and psychological costs associated with the care of AD patients are very high; therefore, significant funds for research in this field are being invested worldwide. The accuracy of medical methods for establishing the diagnosis of AD with specific neuropathology is very important. Biomarkers can detect AD in their pre-clinical stage, monitor the disease progression, and detectmore objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recommended self-management interventions include information on the health condition, the stress management techniques, the physical exercises, the skill to solve personal problems, which allows people diagnosed with osteoarthritis to effectively manage long-term disease symptoms (48). The results of a meta-analysis on 13 studies published in 2009 proved the beneficial effect of self-management programs on pain, the improvement of the quality of life, which would play an important role in the treatment of osteoarthritis (49). The authors of this study presented that the weak effects for self-management programs are represented by the patient's perception of the disease, associated comorbidities and patient's education (50,51).…”
Section: Introductionmentioning
confidence: 84%
“…Recommended self-management interventions include information on the health condition, the stress management techniques, the physical exercises, the skill to solve personal problems, which allows people diagnosed with osteoarthritis to effectively manage long-term disease symptoms (48). The results of a meta-analysis on 13 studies published in 2009 proved the beneficial effect of self-management programs on pain, the improvement of the quality of life, which would play an important role in the treatment of osteoarthritis (49). The authors of this study presented that the weak effects for self-management programs are represented by the patient's perception of the disease, associated comorbidities and patient's education (50,51).…”
Section: Introductionmentioning
confidence: 84%
“…Research has shown the involvement of cytokines, especially of the interleukin -1 and 17, as well as tumor necrosis factor TNF α in stimulating the degradation of some protein, resulting in accelerated cartilage destruction. Doing physical exercises, due to the synthesis of neurotrophins and the improvement of the neuroplasticity has a role in the psychic recovery of the cognition of the patients with osteoarthritis [8].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic therapy has the purpose of preventing the muscular atrophy of the bilateral quadriceps, to tonify the musculature, to repair the dynamic control for a good static posture but also for the walk, to repair the articular mobility (18,19). Moreover, at the psychical level, the physical activity, by the synthesis of neurotrophins and the improvement of neuroplasticity can have a beneficial contribution in the neurodegenerative diseases, respectively in the slight cognitive disorder (20). Cochrane showed in 2015 the importance of the physical activity in order to improve the pain and the functional condition for persons with knee osteoarthritis (21).…”
Section: Introductionmentioning
confidence: 99%
“…We tried this association in our trial, too (27). The indications by Cochrane are for the administration of specific NSAID (Etoricoxibum) for patients who are at gastrointestinal risk (20). It is considered that Etoricoxibum has a more reduced power than the other NSAIDS, but it is preferred as it has fewer side effects (28).…”
Section: Introductionmentioning
confidence: 99%